Cardiac sequelae of acute head injury. Issue 3 (March 1982) - McLeod, A A; Neil-Dwyer, G; Meyer, C H; Richardson, P L; Cruickshank, J; Bartlett, J
Abstract : An intensive 72 hour study of the cardiovascular effects of severe diffuse brain injury was made in seven patients. No other major injury was present. Patients received optimal care very rapidly after injury and intracranial pressure, which was continuously monitored, was maintained at or just above normal by elective positive pressure ventilation techniques. Three patients showed evidence of progressive myocardial ischaemia on continuous electrocardiographic monitoring. Two of these patients died. Ventricular arrhythmias were uncommon but one of the patients with ischaemia developed ventricular tachycardia. Heart rate patterns were very abnormal but did not predict complications. Blood pressure did not vary greatly and cardiac outputs were usually normal. Pronounced excesses of urinary catecholamines and serum creatine kinase 2 isoenzyme (CK MB) as well as total creatine kinase were found. Histological evidence of myocardial damage could be shown at necropsy in the one case whose heart was available for study. This study shows that the cardiac effects of isolated diffuse cerebral injury may be harmful and even fatal despite correction of secondary factors such as anoxia and raised intracranial pressure. The findings suggest that evaluation of the potential benefits of sympathetic blockade is warranted. Cardiac complications of cerebral damage deserve wider recognition by intensive care personnel, neurologists, and neurosurgeons.